Forwand backward electron yield ratio for α-particle induced emission from different materials - Zhurenko, V.P.; Kononenko, S.I.; Kalantaryan, O.V.; Avotin, S.S.; Rokhmanov, N.Ya. (Вопросы атомной науки и техники, 2020)
TIn this work, the ratio of forward and backward electron yields for emission induced by the isotropic flux of α-particles from zinc was measured. On the basis of the measured values and experimental data obtained in earlier experiments for other materials, a systematization of the electron yield ratio for forward and backward emission was done, and a relationship of the ratio with stopping power of an ion in a substance was found. The dependence of work function for various materials on the ratio of the electron emission yields was analyzed.